2003
DOI: 10.1007/bf03325007
|View full text |Cite
|
Sign up to set email alerts
|

Oral manifestations in a group of young patients with anorexia nervosa

Abstract: Anorexia nervosa (AN) is an eating disorder (ED) identified using DSM-IV criteria. Eating disorders are occurring increasingly earlier in childhood and can lead to a series of oral manifestations. The aim of this study was to evaluate the correlation between stomatognathic lesions and eating disorders in 80 young patients (76 females and 4 males aged 9-18 years) with restricting or binge-eating/purging AN. The results confirm the close correlation between ED and oral lesions, the most common of which were dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 22 publications
2
13
0
Order By: Relevance
“…5 Historically, studies describing the effects of eating disorders on oral health have focused on the consequences of the binge-eating/purging behavior subtype. These studies have shown a high prevalence of both tooth enamel erosion 6 and dental caries 7 within this patient group. However, the same attention towards dental health has not been given to patients with restrictive type AN and its potential relation to low bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…5 Historically, studies describing the effects of eating disorders on oral health have focused on the consequences of the binge-eating/purging behavior subtype. These studies have shown a high prevalence of both tooth enamel erosion 6 and dental caries 7 within this patient group. However, the same attention towards dental health has not been given to patients with restrictive type AN and its potential relation to low bone mineral density (BMD).…”
Section: Introductionmentioning
confidence: 64%
“…Both subtypes can have serious medical consequences, including effects on both bone and oral health. [1][2][3][4][5][6][7] Previous studies suggest that a low bone mass is common in adolescent girls and young women with AN and that it may occur early in the course of their disease, compromising peak bone mass. As a result, AN may increase the risk for osteoporosis and fracture throughout life.…”
Section: Introductionmentioning
confidence: 99%
“…Purging behaviors, such as self-induced vomiting, abuse of laxatives, diuretics, and enemas, can occur both after an episode of binge-eating, after eating seemingly normal amounts of food, or as an independent behavior unrelated to food intake. Purging behaviors are associated with substantial medical and dental morbidity (1,2) and constitute a relevant clinical issue.…”
Section: Introductionmentioning
confidence: 99%
“…When symptoms of self-induced vomiting are present, the risk of dental complications is high even after a relatively short history of vomiting [110] and dental reviews are recommended. Common gastrointestinal disturbances include gastric pain, prolonged gastric emptying and constipation [108], all of which can perpetuate the desire to continue restricting.…”
Section: Introductionmentioning
confidence: 99%